Peran Guru dan Orang Tua Dalam Pembelajaran Daring di Sekolah Dasar SDK 060 Riipua - Ere, Elsa; Widia Natasha, Anastasia; Farelino, Gabrielo (Vocat : Jurnal Pendidikan Katolik, 2023)
This study aims to identify the role of teachers and parents in online learning of elementary scholl students as a result of the COVID1- pandemic. Learningcarried out in elementary schools dooring  a pandemic uses online learning throung active at home parental guidance and teachers as innovative online learning materials, so online learning at home students feel happy, have time flexibility to study, can study anytime and anywhere with direction. From the teacher and direct guidance by parents. The role of teachers and parents is very important in online learning. The method used is qualitative research.